Injury risk in Danish youth and senior elite handball using a new SMS text messages approach - Moller, M.; Attermann, J.; Myklebust, G.; Wedderkopp, N. (British Journal of Sports Medicine, 2012)
Objective To assess the injury incidence in elite handball, and if gender and previous injuries are risk factors for new injuries.